SRB's manual of surgery - Bhat M, Sriram (Jaypee Brothers Medical Publishers, 2013)
Brings trainee surgeons the latest procedures and techniques in general surgery, examining common and uncommon disorders in different parts of the body and the surgical procedures used to treat them.